2015
DOI: 10.1038/ng.3356
|View full text |Cite
|
Sign up to set email alerts
|

Genomic landscape of cutaneous T cell lymphoma

Abstract: Cutaneous T cell lymphoma (CTCL) is a non-Hodgkin lymphoma of skin-homing T lymphocytes. We performed exome and whole genome DNA sequence and RNA sequencing on purified CTCL and matched normal cells. The results implicate mutations in 17 genes in CTCL pathogenesis, including genes involved in T cell activation and apoptosis, NFκB signaling, chromatin remodeling, and DNA damage response. CTCL is distinctive in that somatic copy number variants (SCNVs) comprise 92% of all driver mutations (mean of 11.8 pathogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
484
2
21

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 368 publications
(533 citation statements)
references
References 75 publications
(113 reference statements)
26
484
2
21
Order By: Relevance
“…40,45,50 Despite the well-established role of STAT3 in CTCL pathogenesis, it has not been clear what drives malignant STAT3 activation in vivo. Recently, activating mutations have been described in a subset (12.5%) of CTCL patients, 28,29 but it remains unknown what drives aberrant STAT3 activation in the majority of patients. Early on, it was discovered that malignant T cells under ex vivo conditions rapidly lost expression of activated STAT3, indicating that in vivo signals and factors (such as IL-2Rg cytokines) present in the local environment play a key role in malignant STAT3 activation in CTCL patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40,45,50 Despite the well-established role of STAT3 in CTCL pathogenesis, it has not been clear what drives malignant STAT3 activation in vivo. Recently, activating mutations have been described in a subset (12.5%) of CTCL patients, 28,29 but it remains unknown what drives aberrant STAT3 activation in the majority of patients. Early on, it was discovered that malignant T cells under ex vivo conditions rapidly lost expression of activated STAT3, indicating that in vivo signals and factors (such as IL-2Rg cytokines) present in the local environment play a key role in malignant STAT3 activation in CTCL patients.…”
Section: Discussionmentioning
confidence: 99%
“…13,24 Activating mutations are sufficient to turn STAT3 into a full oncogene in experimental animals, 10 and activating mutations in Janus kinases (JAKs) have been described in other hematologic malignancies. [25][26][27] Recently, activating mutations have also been described in a subset (12.5%) of CTCL patients, 28,29 but it remains unknown what drives aberrant activation of JAK/STAT signaling in the majority of patients. STAT3 activation may become further increased after loss of regulatory control by suppressor of cytokines signaling 3, by protein inhibitor of activated STAT3, and by other tyrosine protein phosphatases.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] These studies have now confirmed, expanded, and functionally validated many of the genetic aberrations detected by aCGH in MF/SS, a broad and diverse spectrum that include genes associated with T-cell receptor (TCR) signaling, activation of NF-kB, JAK/STAT signaling, chromatin remodeling, and DNA damage response. However, despite a significant degree of overlap, there was great variability in the identity and frequency of alterations at putative driver genes across studies.…”
mentioning
confidence: 70%
“…However, despite a significant degree of overlap, there was great variability in the identity and frequency of alterations at putative driver genes across studies. For example, some studies identified loss-of-function mutations or deletions of TCF8/ZEB1 in 56% to 65% of cases, 2,5,6 whereas others did not. 4 By compiling the published NGS data from 220 MF/SS patients, and subjecting them to a uniform statistical analysis, Park et al were able to achieve a sample size adequate to identify 55 putative driver genes, including novel mutations at 17 genes, 5 of which had never been involved in cancer.…”
mentioning
confidence: 99%
“…To this end, Dr. Vaque's group designed specific cancer-type approaches, consisting of a combination of NGS techniques used alongside other tools commonly employed in diagnosis, such as, immunohistochemistry (IHC), and pre-clinical/clinical research (i.e., patient-derived xenograft in vivo models and a clinical trial respectively). For CTCL they identified important mechanisms of tumorigenesis and progression of CTCL regarding PLCG1-downstream signaling as activating mutations in PLCG1, NFKB (CARD11 and RELB) and JAK/STAT (38,39), as well as amplifications in PRKCQ (40). For MM they developed a targeted NGS approach (exons from 217 genes) that enabled the rapid detection (15 days) of important mechanisms of MM disease, as well as case-specific combinations of targeted inhibitors, tested ex vivo and in vivo, that proved to be more effective when used in appropriate mutational backgrounds (41).…”
Section: Guess Labsmentioning
confidence: 99%